Generalized Exponential Type Estimator for Population Variance in Survey Sampling - AMBER ASGHAR; AAMIR SANAULLAH; MUHAMMAD HANIF (Revista Colombiana de Estadística, 2014)
In this paper, generalized exponential-type estimator has been proposed for estimating the population variance using mean auxiliary variable in single-phase sampling. Some special cases of the proposed generalized estimator have also been discussed. The expressions for the mean square error and bias of the proposed generalized estimator have been derived. The proposed generalized estimator has been compared theoretically with the usual unbiased estimator, usual ratio and product, exponential-type ratio and product, and generalized exponential-type ratio estimators and the conditions under which the proposed estimators are better than some existing estimators have also been given. An empirical study has also been carried out to demonstrate the efficiencies of the proposed estimators.